Polyelectrolytes Multilayers to Modulate Cell Adhesion: A Study of the Influence of Film Composition and Polyelectrolyte Interdigitation on the Adhesion of the A549 Cell Line - Muzzio, Nicolas E.; Pasquale, Miguel A.; Gregurec, Danijela; Diamanti, Eleftheria; Kosutic, Marija; Azzaroni, Omar; Moya, Sergio E. (Macromolecular Bioscience, 2016)
Polyelectrolyte multilayers (PEMs) with different polycation/polyanion pairs are fabricated by the layer-by-layer technique employing synthetic, natural, and both types of polyelectrolytes. The impact of the chemical composition of PEMs on cell adhesion is assessed by studying cell shape, spreading area, focal contacts, and cell proliferation for the A549 cell line. Cells exhibit good adhesion on PEMs containing natural polycations and poly(sodium 4-styrenesulfonate) (PSS) as polyanion, but limited adhesion is observed on PEMs fabricated from both natural polyelectrolytes. PEMs are then assembled, depositing a block of natural polyelectrolytes on top of a stiffer block with PSS as polyanion. Cell adhesion is enhanced on top of the diblock PEMs compared to purely natural PEMs. This fact could be explained by the interdigitation between polyelectrolytes from the two blocks. Diblock PEM assembly provides a simple means to tune cell adhesion on biocompatible PEMs. Biocompatible surfaces with improved cell adhesion are obtained by diblock polyelectrolyte multilayers (PEMs). On the basis of cell adhesion studied on a large number of PEMs made of natural and synthetic polyelectrolytes, a diblock PEM is fabricated by combining a block of soft natural polyelectrolytes on the top of a stiffer block containing poly(sodium 4-styrenesulfonate) as polyanion.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Adhesion; Biocompatibility; Mechanical properties; Polyelectrolytes; tissue engineering